A Study on the Local Dissemination and Continuity of Christianity in Southwest China: A Case Study of Sichuan and Guizhou Parish of the Christian and Missionary Alliance (1934-1949) - NI, Buxiao (Journal of Research for Christianity in China (JRCC), 2023)
From 1934 to 1949, the development of the Sichuan and Guizhou Parish of the Christian and Missionary Alliance showed that, as the only Christian missionary in the eastern part of Sichuan and Guizhou, the missionaries committed themselves to evangelizing and saving people's souls with local Christians. At the same time, the localization process of the Christian and Missionary Alliance in the eastern part of Sichuan and Guizhou is an important symbol of the success of its dissemination. The purpose of this paper is to explore how the Christian and Missionary Alliance achieved localization in marginal areas, that is, to promote the belief identification and practice mechanism of local Christians to save souls. Leaving the definition of localized church and no longer promoting missionary mission is not a localized form of evangelical mission in a strict sense, nor does it conform to the characteristics of independent churches of the Christian and Missionary Alliance. Therefore, the contact between the Christian and Missionary Alliance and the local people shows that the process from "foreign" to "local" not only realizes the goal of local independence but also shows the phenomenon of the inheritance of Christianity in China.
Keywords: The Christian and Missionary Alliance, Sichuan and Guizhou region, localization, evangelism, inheritance mechanism